How Do Working-Class People in China Comment on Chinese-Language Buddhist Films? - Sun, Zhentao (Religions, 2022)
The dissemination and acceptance of Chinese-language Buddhist films in China have not yet received much attention. This paper takes four Chinese-language Buddhist films as samples to analyze the Buddhist doctrines they contain and how they are reviewed by the Chinese working class. It points out that most Chinese working-class people are not Buddhists, their knowledge of Buddhist doctrines is relatively small and shallow, and they rely on their daily life experiences when enjoying Buddhist films, so they cannot understand Buddhist doctrines in Buddhist films that are too difficult or contrary to their daily life experiences. It argues that Chinese-language Buddhist films need to balance the missionary aspirations of Buddhism with the popular attributes of cinema so as to enhance the appeal and influence of Buddhism among the working class.